Phantai Narasingha: Reproduction in Contemporary Thai Society - Limlertsathien, Paramaporn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
This article aims to study the reproduction of Phantai Narasingha in present Thai society. The findings show that various forms of Phantai Narasingha reproduction can exemplify how traditions are created by applying and interpreting the local history in the new contexts. This reflects the condition of cultural dynamics which have been changed due to the social contexts, particularly the contexts of tourism and capitalism. These changes can be seen through the reproduction of amulets and films responding to the capitalism world or the organization of provincial tourism festivals such as ‘City of Honesty’, ‘Wedding Ceremony’, and ‘Marathon for Honesty’. Phantai Narasingha worship ceremony is another strategy used to create provincial identity through local historical tales. It can be said that these activities are all responding to the country’s tourism policy. Besides these, the reproduction of Phantai Narasingha has resulted in the community development in various aspects as well as building up people’s awareness which helps strengthen the community.